Montrer l’engagement des femmes pour l’environnement au Mexique et en Argentine - Marion Gautreau (L'Ordinaire des Amériques)
Julio Pantoja, an Argentine national, has been a photojournalist for more than thirty years. Recurrent themes in his work are the memory of the dictatorship (1976-1983) and the defense of human and environmental rights. In 2007, he produced the Las madres del monte project on deforestation for extensive soybean cultivation in northern Argentina, and the mobilization of women living in the area in the face of this devastating process for their day-to-day environment. In the same vein, Julio Pantoja travelled to Mexico in 2011 to photograph women activists committed to protecting the “original corn”, a staple of the Mexican diet. This project, entitled Mujer, maíz y resistencia, uses the same photographic device as his previous project: portraits of women posing against a light background in landscapes. Through the study of these two series, we will question the way in which the photographer underlines the importance of women’s activism in the face of threats to food and agroforestry habits in Mexico and Argentina.